2022
DOI: 10.1002/ldr.4433
|View full text |Cite
|
Sign up to set email alerts
|

Plateau pika burrowing and yak grazing jointly determine ecosystem greenhouse gas emissions of alpine meadow

Abstract: Domestic yak (Bos grunniens) have coexisted with plateau pika (Ochotona curzoniae) for thousands of and they play irreplaceable roles in shaping the structure and function of alpine meadow ecosystem. However, the mechanisms whereby the greenhouse gas (GHG) emissions change in response to the interactive effects between yak grazing and plateau pika burrowing remain unclear. In this study, we examined the response of ecosystem GHG emissions (CO 2 , CH 4 , and N 2 O flux) to yak grazing and pika burrowing in alpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Meanwhile, analysis methods included multiple innovation model combinations as well as meta‐analysis. SD: system dynamics, GIS: geographic information systems, RF Model: random forest model, DNDC Model: denitrification‐decomposition (DNDC) model (Bhardwaj et al, 2022; Chen et al, 2022; Feng et al, 2023, Hashimi et al, 2022; He et al, 2022; Jia et al, 2023; Liu et al, 2022; Ravisankar et al, 2022; Wang et al, 2022, 2023; Xu et al, 2022; Yang et al, 2022, Zhang et al, 2022, 2023). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, analysis methods included multiple innovation model combinations as well as meta‐analysis. SD: system dynamics, GIS: geographic information systems, RF Model: random forest model, DNDC Model: denitrification‐decomposition (DNDC) model (Bhardwaj et al, 2022; Chen et al, 2022; Feng et al, 2023, Hashimi et al, 2022; He et al, 2022; Jia et al, 2023; Liu et al, 2022; Ravisankar et al, 2022; Wang et al, 2022, 2023; Xu et al, 2022; Yang et al, 2022, Zhang et al, 2022, 2023). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Figurementioning
confidence: 99%
“…Through transect survey, it was found that precipitation use efficiency mediated plant biomass allocation in arid and semi‐arid ecosystems; such a finding provides insights into the complex mechanisms of ecological processes (Feng et al, 2023). Specifically, the effects of soil nematode community, plateau pika burrowing, and yak grazing on greenhouse gas emissions cannot be discounted in alpine grassland ecosystems (Wang et al, 2022, 2023). These findings support our goal of building a sustainable and resilient grassland ecosystem worldwide (Sun et al, 2022).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Less attention has been devoted to lighter (‘small’) terrestrial herbivorous mammals (body mass <~5–10 kg), in spite of their important influence on ecosystem function and structure (Bomske & Ahlers, 2021; Dickman, 1999). Small herbivores can change soil properties including moisture, carbon and nitrogen content through bioturbation (e.g., burrowing and soil redistribution), consumption and excretion, which can alter above and below‐ground plant biomass and in greenhouse gas emissions (Wang, Pang, & Guo, 2022; Wang, Sun, et al., 2022). Overall, the sphere of influence of small mammals appears comparable to larger animals as it includes nutrients, carbon cycling and greenhouse gas fluxes (Poe et al., 2019; Wang, Pang, & Guo, 2022; Wang, Sun, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%